Biodiversity of vertebrates in Argentina: patterns of richness, endemism and conservation status - Bauni, Valeria (2022)
Optimising conservation efforts requires an accurate record of the extant species as well as their geographic distributions. Nevertheless, most current conservation strategies start from an incomplete biodiversity inventory. Argentina has an extraordinary diversity of species, however, until now an updated inventory of its fauna has not been carried out. In this context, the main objective of this work is to present the results of the first national inventory of vertebrate species. Experts from each major vertebrate taxonomic group assembled and compiled its respective inventory. The information gathered included taxonomic rank, conservation status, endemism and geographic distribution. Species richness and representativeness were calculated for each taxonomic group, distinguishing between native, endemic and exotic, for each Argentinian province. Our results show Argentina harbours 3,303 species: 574 marine fish, 561 freshwater fish, 177 amphibians, 450 reptiles, 1,113 birds, and 428 mammals. Native species constitute 98.1% of the total taxa. The results achieved were spatially represented showing a pattern of higher richness from north to south and from east to west. Species considered as threatened account for 17.8% and 15.2% are endemic. There are five Extinct species. These results provide key information on developing strategies and public policies at the national and provincial levels and constitute a tool for the management and conservation of biodiversity.